The regulation of cell homeostasis and antiviral innate immunity by autophagy during classical swine fever virus infection. Issue 1 (31st December 2023) - Li, Xiaowen; Song, Yiwan; Wang, Xinyan; Fu, Cheng; Zhao, Feifan; Zou, Linke; Wu, Keke; Chen, Wenxian; Li, Zhaoyao; Fan, Jindai; Li, Yuwan; Li, Bingke; et al.
ABSTRACT: CSFV (classical swine fever virus) is currently endemic in developing countries in Asia and has recently re-emerged in Japan. Under the pressure of natural selection pressure, CSFV keeps evolving to maintain its ecological niche in nature. CSFV has evolved mechanisms that induce immune depression, but its pathogenic mechanism is still unclear. In this study, using transcriptomics and metabolomics methods, we found that CSFV infection alters innate host immunity by activating the interferon pathway, inhibiting host inflammation, apoptosis, and remodelling host metabolism in porcine alveolar macrophages. Moreover, we revealed that autophagy could alter innate immunity and metabolism induced by CSFV infection. Enhanced autophagy further inhibited CSFV-induced RIG-I-IRF3 signal transduction axis and JAK-STAT signalling pathway and blocked type I interferon production while reducing autophagy inhibition of the NF-κB signalling pathway and apoptosis in CSFV infection cells. Furthermore, the level of CSFV infection-induced glycolysis and the content of lactate and pyruvate, as well as 3-phosphoglyceraldehyde, a derivative of glycolysis converted to serine, was altered by autophagy. We also found that silencing HK2 (hexokinase 2), the rate-limiting enzyme of glycolytic metabolism, could induce autophagy but reduce the interferon signalling pathway, NF-κB signalling pathway, and inhibition of apoptosis induced by CSFV infection. In addition, inhibited cellular autophagy by silencing ATG5 or using 3-Methyladenine, could backfill the inhibitory effect of silencing HK2 on the cellular interferon signalling pathway, NF-κB signalling pathway, and apoptosis.